Coordination difficulties in preschool-aged children are associated with maternal parenting stress: A community-based cross-sectional study. (November 2017) - Takahashi, Michio; Adachi, Masaki; Takayanagi, Nobuya; Yasuda, Sayura; Tanaka, Masanori; Osato-Kaneda, Ayako; Masuda, Takahito; Nakai, Akio; Saito, Manabu; Kuribayashi, Michito; Nakamura, Kazuhiko
Highlights: We examined coordination difficulties in children and maternal parenting stress in a community-based sample in Japan. Coordination difficulties are a significant predictor of parenting stress. Impaired general coordination is one of the strongest predictors of parenting stress. The pattern of impact of coordination difficulties differs between boys and girls. Coordination difficulties show an association with ADHD and ASD traits. Abstract: Background: Although coordination difficulties are sometimes observed even in children in the general population, no empirical studies have examined the impact of these difficulties on parenting stress. Aims: The aim of this study was to elucidate the relationship between coordination difficulties and parenting stress in a community-based sample of preschool-aged children and their mothers. Methods: The study included 1691 families. Mothers with 4- or 5-year-old children completed questionnaires about parenting stress and children's coordination difficulties, as well as traits associated with attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Results: The results of hierarchical multiple regression analyses showed that coordination difficulties, and ADHD and ASD traits were each independent predictors of parenting stress. Among the significant predictive factors, impaired general coordination, as well as hyperactivity-impulsivity, showed a strong impact on parenting stress. In addition, a gender difference was observed in the manner in which coordination difficulties influenced parenting stress. Conclusions: Coordination difficulties in preschool-aged children in the general population increased maternal parenting stress (as did ADHD and ASD traits). This highlights the need to provide support for mothers who have children with coordination difficulties, even when there is no clinical diagnosis.